BRAIN DANCE SEBAGAI ALTERNATIF STIMULI UNTUK MENUMBUHKAN RASA PERCAYA DIRI - Sari, Dyan Indah Purnama; Prayogo, Muhaimi Mughni; Saraswati, Ayu Ridho (Universitas Sarjanawiyata Tamansiswa, 2020)
Brain Dance was first introduced by Anne Green Gilbert, a creative dance maestro from Washington DC. Brain Dance is an apperception to activate human body parts. Brain Dance acts as a stimulant to connect the performance of the brain, breathing, motoric, and sensory body so that it is ready to move. In the creative dance process, Brain Dance is the first step so that children are ready, not only physically but also psychologically ready. Besides activating the body, Brain Dance also provides a feeling of freedom and happiness and fosters self-confidence. Brain Dance is suitable for all ages, as well as PGSD UST Yogyakarta students as the subject of this study. Students of PGSD’s 7th semester, in particular, are aged between 20-23 years and nearly 90% cannot dance. Never having danced before, and being unable to dance will be the reasons for the inferiority, shame, and insecurity, which will affect the effectiveness of body movements. The research method used is descriptive qualitative, to describe the condition of the data as it is, through the process of observation, interviews, and documentation. Through Brain Dance, this research is expected to foster self-confidence in PGSD UST Yogyakarta students in activating the body in the creative dance work process.